Increased concentration of aluminium in the brain of a parenterally fed preterm infant. Issue 9 (September 1989) - Bishop, N J; Robinson, M J; Lendon, M; Hewitt, C D; Day, J P; O'Hara, M
Abstract : Parenteral feeding solutions currently used for preterm infants are contaminated with aluminium. We report the case of an infant who was fed parenterally for 45 days, who died aged 3 months, and who had a considerably increased concentration of aluminium in his brain tissue at necropsy.